ANALISIS PENERIMAAN DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus pada Dinas Pendapatan Pengelolaan Keuangan dan Aset Kabupaten Sukoharjo Tahun 2011 â 2015) - Muhammad Rofiq Sunarko, Mirna Suwanti, Suharno & (Akuntansi, 2017)
The purpose of this study was to analyze the effectiveness, efficiency and taxcontribution in Sukoharjo district from 2011-2015. This research is a case study inSukoharjo district. The type of data using quantitative and qualitative data. Sourcesof data using secondary sources. The technique of collecting data used interviews,documentation and observation. Data were analyzed used effectiveness ratio,efficiency ratio and the ratio of contributions. The results showed the averageeffective tax revenues in the years 2011-2015 Sukoharjo said to be effective as apercentage effectiveness by 124.97%. The average efficiency ratio Sukoharjoregency hotel tax revenue in 2011-2015 is said to be sufficient. The average rate ofgrowth of tax revenue in Sukoharjo district during the last five years are the years2011-2015 shows the growth rate of 66,71% that expressed less successful.Keywords: effectiveness, efficiency, contribution, hotel taxes